Application of Activty Learning Method (ALM) to Improve Basketball Dribbling Skills - Zumrudatul Alwiyah Alwiyah; Afifan Yulfadinata (Sekolah Tinggi Olahraga dan Kesehatan Bina Guna, 2026)
This study aims to analyze the effectiveness of the Activity Learning Method (ALM) to improve the basketball dribbling skills of MTsn 2 Sidoarjo students. Initial observations show that most students have difficulty in dribbling due to lack of variety and have not fully implemented structured motor activities. This study uses a quasi-experiment using a one group pretest posttest model involving 32 students in grade IX h who were selected using the purposive sampling technique. Over the course of six weeks, students participate in a series of hands-on experiential learning activities that emphasize repetitive practice and optimal physical engagement. The results of this study show a significant increase in dribbling ability. It is marked by an increase in the average score from 39.58 in the pretest to 66.25 in the posttest (P-value, 0.000). Further analysis showed that the speed indicator and the number of errors had changed significantly, while ball control showed no significant improvement. These findings confirm that ALM is able to have a positive impact on the development of dribbling skills through a systematic, participatory, and activity-centered approach to students. Thus, this method can be used as an effective learning alternative in the development of basic basketball skills in the madrasah environment.